PERSEPSI MASYARAKAT TERHADAP MANDI BALIMAU KASAI DI KELURAHAN MUARALEMBU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Irmawa, Hendri Putra; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was background Balinese crescent balimau is one of the traditions of hereditary customs of the community's ancestors in Muaralembu urban village, where this custom is still maintained today. But unfortunately at this time, it is seen when researchers do Obserpasi and interview the field, bathing balimau kasai more violated, men with women have mixed even when bathing a lot wearing clothes that are not polite, no longer show on purify themselves the real thing, which can be seen from year to year balimau kasai bath has been tarnished by contradictory actions and bersembarang with Islamic shari'ah such as pretending, riding a man with women, drunk - intoxicated to music that keeps the community from remembering the values Religion or Moral. Objective of research Knowing Perception of society about balimau kasai bath according to adat of Muaralembu Sub-District Singingi Subdistrict, (2) How is the shift of values towards Balimau Kasai Tradition in Muaralembu Sub-District Singingi Sub-district? (3) To know what factors influenced the shift of religious and moral values to balimau kasai bathing tradition in Muaralembu Subdistrict of Singingi Subdistrict. This research is a quantitative research. Objective of research Knowing Perception of society about balimau kasai bath according to adat of Muaralembu Sub-District Singingi Subdistrict, (2) How is the shift of values towards Balimau Kasai Tradition in Muaralembu Sub-District Singingi Sub-district? (3) To know what factors influenced the shift of religious and moral values to balimau kasai bathing tradition in Muaralembu Subdistrict of Singingi Subdistrict. This research is a quantitative research. Data were analyzed by combining data obtained from the field research results with data obtained from the source of related institutions. Result of research of Public Perception on Balimau Kasai Bath in Muaralembu Village preparation of balimau bath, balimau kasai bath. Factors influencing changes in balimau kasai bath internal factors and external factors, internal factors that coordination of the committee is much different when compared from the previous year, Location of Balimau Kasai Muaralembu Bath tradition implementation, Lack of agree between Datuak - Datuak Adat Pemangku with Balimau Kasai Bath Committee , while the external factors Influence Of Foreign Culture, polluted river.Keywords: Public Perception, Balimau Kasai bath, Muaralembu